2020
DOI: 10.1039/d0cp02718a
|View full text |Cite
|
Sign up to set email alerts
|

All-perylene-derivative for white light emitting diodes

Abstract: An organic-based bright white light emitting compound, namely Tb(H3PTC)3, able to be used as part of a white diode and as a part of a RGB system that can withstand...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Tb(H 3 PTC) 3 shows net magnetic moment, has high fluorescence quantum yield, and its fluorescence in the solid state ranges from green to red, depending on the film thickness. [18] In that work, we showed that this characteristic emission comes from two processes, one scattering involving the exciton with a phonon and an electron and the consequent changing of the molecular Hamiltonian due to the photoinduced charge transfer (PCT) of the scattered electron, both in the neutral and the charged molecules involved in the PCT process. [18] However, the slow variation of the emission peak of the spectra with the film thickness, instead of an abrupt change in energy, could not be explained solely by the processes described above.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Tb(H 3 PTC) 3 shows net magnetic moment, has high fluorescence quantum yield, and its fluorescence in the solid state ranges from green to red, depending on the film thickness. [18] In that work, we showed that this characteristic emission comes from two processes, one scattering involving the exciton with a phonon and an electron and the consequent changing of the molecular Hamiltonian due to the photoinduced charge transfer (PCT) of the scattered electron, both in the neutral and the charged molecules involved in the PCT process. [18] However, the slow variation of the emission peak of the spectra with the film thickness, instead of an abrupt change in energy, could not be explained solely by the processes described above.…”
mentioning
confidence: 99%
“…The calculations showed a series of discrete energy levels near the Fermi energy, corresponding to Tb f orbital, which would be the expected result but for every example in the literature reported so far for Tb 3 + mono metal complexes, being the only exception Tb-(H 3 PTC) 3 . [18] The calculations for Tb(H 3 PTC) 3 show that the ligands closest to the terbium atom are characterized by the presence of a À COO group and a carboxyl group, À COOH. Two ligands bind to the terbium through the available oxygen atoms, both oxygen atoms from À COO and one of the À COOH, as indicated by the red arrows in Figure 1, while the third ligand uses only oxygen atoms from À COO to make the bond (blue arrows in Figure 1), keeping the carboxyl group farther from the terbium atom.…”
mentioning
confidence: 99%
See 3 more Smart Citations